Pelatihan Barbershop dalam Upaya Menumbuhkan Kemandirian Wirausaha Peserta Pelatihan di SKB Sidoarjo - Alisiyah, Mamik Eliva; Nugroho, Rivo (J+PLUS UNESA, 2024)
Barbershop training develop people to increase their knowledge and skills in cutting hair and develop the potential of the community to prepare for the future and be able to grow the entrepreneurial independence of training participants. The aim of this research is to describe and analyze the barbershop training process at SKB Sidoarjo, analyze the supporting factors for barbershop training at SKB Sidoarjo, analyze the inhibiting factors for barbershop training at SKB Sidoarjo, describe and analyze the results of barbershop training on the entrepreneurial independence of training participants at SKB Sidoarjo. This study used qualitative research methods. The research results showed that the barbershop training was carried out well. The supporting factor for the implementation of barbershop training at SKB Sidoarjo is the infrastructure provided by SKB. Factors inhibiting barbershop training include obstacles in terms of the lack of time required to carry out the training. In its implementation, training participants who take part in barbershop training at SKB Sidoarjo gain experience, knowledge and skills in the field of barbershop/haircutting.